A passos silenciosos, a velhice avança na sua direção: Funpresp-Exe versus Tesouro Renda+ - Leal, Roger (2024)
The search for an economically sustainable pension system has resulted in a transfer of risks from the Union to workers. One of the effects of the pension reforms already implemented is the reduction in income for federal public servants in the executive branch upon retirement. As an alternative, these workers may join the Executive Federal Public Servant Complementary Pension Foundation (Funpresp-Exe). However, enrollment in this entity is not mandatory and is not the only option in pension planning. Although there are two studies in the literature that compared investments in Funpresp-Exe with other types of applications, this research innovates by aiming to analyze the advantages and disadvantages of choosing to invest in the Funpresp plan compared to the public bond Tesouro RendA+. This is a descriptive study. In terms of the research approach, a pragmatic philosophical perspective was proposed, with a quantitative focus on applying descriptive statistics and prescriptive data analysis. The findings highlight differences in returns between males and females and between those who started investing in their pension plan as soon as they entered public service compared to those who started later. The simulation results show that, to achieve the same monthly retirement income, 25-year-old servants of both genders would need to make smaller monthly contributions if they opted for Tesouro RendA+. On the other hand, for 45-year-old servants, both men and women, investing through the Funpresp-Exe plan would require smaller contributions. The analysis of the bibliographic and documentary survey indicates that public bonds are safer. On the other hand, complementary pension plans offer differentiated benefits that may be attractive. It is expected that the publication of this study and the eventual implementation of the intervention plan will raise awareness among federal public servants in the executive branch about the importance of the pension issue and assist them in decision-making.